Functional Interactions Between the Parafascicular Thalamic Nucleus and Motor Cortex Are Altered in Hemiparkinsonian Rat - Li, Min; Zhang, Xiao; He, Qin; Chen, Dadian; Chen, Feiyu; Wang, Xiaojun; Sun, Shuang; Sun, Yue; Li, Yuchuan; Zhu, Zhiwei; Fang, Heyi; Shi, Xiaoman; et al. (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is characterized by aberrant discharge patterns and exaggerated oscillatory activity within basal ganglia-thalamocortical circuits. We have previously observed substantial alterations in the spike and local field potential (LFP) activities recorded in the thalamic parafascicular nucleus (PF) and motor cortex (M1), respectively, of hemiparkinsonian rats during rest or catching movement. The current study explored whether the mutual effects of the PF and M1 depended on the amplitude and phase relation within their identified neuron spikes or group rhythmic activities. Microwire electrode arrays were paired and implanted in the PF and M1 of rats with unilateral dopaminergic cell lesions. The results showed that identified PF neurons exhibited aberrant cell type-selective firing rates and preferentially and excessively phase-locked firing to cortical LFP oscillations mainly at 12-35 Hz (beta frequencies), consistent with the observation of identified M1 neurons with ongoing PF LFP oscillations. Experimental evidence also showed a decrease in phase locking at 0.7-12 Hz and 35-70 Hz within the PF and M1 circuit in hemiparkinsonian rats. Furthermore, anatomical evidence was provided for the existence of afferent and efferent bidirectional reciprocal connectivity pathways between the PF and M1 using an anterograde and retrograde neuroanatomical tracing virus. Collectively, our results suggested that multiple alterations may be present in regional anatomical and functional modes by which the PF and M1 interact with and that parkinsonism-associated changes in PF integrate M1 activity in a manner that varies with the frequency, behavioral state, and the integrity of the dopaminergic system.